The Role of Corporate Social Responsibility (CSR) of PT. Phi Balam in Realizing the Sustainable Development Goals (SDGs) - P. Darmawan Laoli; Zainal Abidin Pakpahan; Muhammad Yusuf Siregar (International Journal of Science and Environment (IJSE), 2026)
Corporate Social Responsibility (CSR) is a company's social obligation as mandated by Law No. 40 of 2007 concerning Limited Liability Companies and various other environmental regulations. PT. PHI Balam, as a company operating in the forestry/plantation sector, has a significant responsibility to ensure that its operational activities are not only profit-oriented but also contribute to sustainable development. This study aims to analyze the role of PT. PHI Balam's CSR in realizing the Sustainable Development Goals (SDGs), especially in the aspects of the environment, education, health, and community economic empowerment. The results of the study indicate that PT. PHI Balam's CSR has contributed to several SDGs indicators through community empowerment, environmental conservation, and social development programs, although continuous evaluation is needed to ensure their implementation is more focused and measurable. These programs make a significant contribution to the goals of the SDGs, including environmental preservation, improving community economic welfare, and community health and nutrition in the company's concession area. Through these concrete steps, PT. PHI Balam demonstrates a real commitment to realizing inclusive and effective sustainable development.